Hubungan Tingkat Konsumsi Energi Dan Status Gizi Dengan Indeks Prestasi Belajar Pada Siswa Di SMP Negeri 2 Semarapura - Riska Muyassarah; I Wayan Ambartana; I Gusti Agung Ari Widarti (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Student learning achievement is influenced by various factors, including nutritional intake and nutritional status. Adequate energy consumption and good nutritional status are believed to play an important role in supporting optimal concentration and cognitive function. This study aims to determine the relationship between energy consumption levels and nutritional status with student learning achievement index at Junior High School 2 in Semarapura. This study used an observational method conducted in February - May at Junior High School 2 in Semarapura involving 55 samples. The population of this study was grade VIII students of Junior High School 2 in Semarapura in the year 2024/2025, samples were taken using the simple random sampling method and purposive sampling technique. Data on energy consumption levels were taken through recall forms, nutritional status data were taken by measuring and weighing, and learning achievement data were taken through odd semester report cards. Statistical tests used the Spearman rank test. The average energy consumption of the sample was 1,972 kcal with 46 samples (83.6%) included in the good energy consumption group, the nutritional status of the samples was mostly normal, namely 44 samples (80%) and the learning achievement of the samples (100%) was classified as good. The results showed a significant relationship between the level of energy consumption and nutritional status with the achievement index.